1961
DOI: 10.1002/pol.1961.1205115612
|View full text |Cite
|
Sign up to set email alerts
|

Changes in orientation of crystallites during stretching and relaxation of polyethylene films

Abstract: A microbeam camera has been used in x‐ray diffraction studies of the changes which occur in orientation of crystallites in polyethylene film when the film is stretched and later relaxed. The collimator of the microbeam camera, 100 μ in diameter, allows one to follow the orientation changes very closely in the necked‐down region of a stretched sample. The stretching of polyethylene proceeds by alignment of the a‐axes of the crystallites perpendicular to the stretching direction with the planes containing b‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…This is in line with findings for melt-crystallized PE samples at very low draw ratios [21][22][23][24][25][26]. 1.1, the 200 reflection almost immediately exhibits an equatorial maximum in addition to two reflection arcs on both sides of the equator.…”
Section: Wide Angle X-ray Scatteringsupporting
confidence: 90%
“…This is in line with findings for melt-crystallized PE samples at very low draw ratios [21][22][23][24][25][26]. 1.1, the 200 reflection almost immediately exhibits an equatorial maximum in addition to two reflection arcs on both sides of the equator.…”
Section: Wide Angle X-ray Scatteringsupporting
confidence: 90%
“…Aggarwal has given the explanation that the splitting of the (110) reection is due to imperfect orientation of b-and c-axis with respect to the stretching direction, i.e., there are considerable wobble of the b-and c-axis. 51 The four-arc pattern is not very obvious in our results, but the splitting of (110) reection and subsequent approaching can also be observed, which is presented and discussed in detail later. At the onset strain of 600%, (010) reection of the strain-induced monoclinic crystals emerges on the equator between amorphous ring and (110) reection in WAXD patterns, exhibiting a highly ordered but relatively diffuse point-like reection.…”
Section: Structural Analysis By Waxd During Deformationsupporting
confidence: 55%
“…Different approaches like mechanical stretching [ 28 ], electric field [ 29 , 30 , 31 ] and magnetic field [ 32 , 33 , 34 ] have been used for orientation of nanofillers. Mechanical stretching has been used for alignment of both the polymer matrix [ 35 , 36 ] and dispersed filler material [ 37 , 38 ]. Amy et al reported an enhancement in k by a factor of 18 in epoxy-CNT composites with densely aligned arrays of CNTs [ 39 ].…”
Section: Introductionmentioning
confidence: 99%